Ford, Chrysler, and General Motors: the fall and rise of an automotive empire - Bardwick, Judith M. (Henry Stewart Talks, 2018)
This case study examines Ford, Chrysler, and General Motors’ complacency in the face of rising competition from Japanese car companies. Following the 1973 oil embargo, this competition could no longer be ignored, and the 3 largest American automobile manufacturers began cutting costs by outsourcing labour. This resulted in increased unemployment and contributed significantly to Detroit declaring bankruptcy in 2013.